USULAN DESIGN SUB LINE TIPE BE 0: STUDI KASUS PADA PT âXYZâ - Budiastuti, Dyah; Pribadi, Teguh Adhi (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
A long with the increasing of market demand on XYZ company product, it will be opened a new design sub line in Surabaya. The purpose of this article is to give working station design suggestion and design sub line working element for production capacity 450 unit/day and measuring efficiency on every working station. That is why, it need a follow up research to get the description of the problems. The problems can be identified after that and then start with data collection that consist of company general data, working element data, and working measure data that collect from direct measurement using stopwatch. After the data is collected, the next step is process data to be use as a basic planning in developing working station.